2015
DOI: 10.1007/s00270-015-1175-3
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Term Outcomes of Endovascular Treatment for TASC-II D Femoropopliteal Occlusive Disease with Critical Limb Ischemia

Abstract: Endovascular treatment for TASC II D lesions is safe and offers satisfying outcomes. This patient subset would benefit from a minimally invasive approach. Follow-up is advisable due to a high rate of restenosis. Further follow-up is necessary to know the long-term efficacy of these procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…This study includes one of the largest series of patients with TASC II D femoropopliteal lesions treated exclusively with endovascular techniques. 7,8,10,15,22 Furthermore, this is the only article exclusively including patients with critical limb ischemia. Because of this characteristic, the cohort was homogeneous and enabled subgroup analyses with a low possibility of bias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study includes one of the largest series of patients with TASC II D femoropopliteal lesions treated exclusively with endovascular techniques. 7,8,10,15,22 Furthermore, this is the only article exclusively including patients with critical limb ischemia. Because of this characteristic, the cohort was homogeneous and enabled subgroup analyses with a low possibility of bias.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] In certain cases, however, an endovascular approach can be the best option, especially for high-risk patients. 5,[7][8][9][10][11][12][13] Recent advancements in endovascular techniques and technologies have overcome many technical limitations, and more complex lesions can be successfully treated. 12 In this context, many patients with extensive lesions are now considered for an endovascular-first strategy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous advances in endovascular techniques and materials have made complex lesions treatable and have led surgeons to attempt an endovascular first strategy in both the inflow and outflow lower extremity arteries. 10,11 However, open CFA endarterectomy remains the gold standard for several reasons, including nature of the plaque, an unfavourable stenting zone being located in a highly flexible area, simultaneous profundaplasty to optimise the runoff, and to provide an access point for inflow and/or outflow endovascular treatment. 12 Initial reports of hybrid procedures date from the 1970s.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these patients often show significant surgical contraindications, such as coronary heart disease and cerebral infarction, that increase the risks associated with surgical revascularization. Numerous clinical studies have shown that EVT is effective in treating TASC II C and D lesions (3)(4)(5)(6)(7)(8)(9). However, while EVT can successfully restore blood flow and improve clinical symptoms, studies have not systematically assessed the correlations between postoperative recurrence and potential risk factors, such as sex, age, smoking, underlying diseases [e.g., diabetes mellitus (DM)], the severity of ischemic symptoms, and TASC classification.…”
Section: Introductionmentioning
confidence: 99%